Hansen’s disease in Brazil: Monitoring of disabilities - Alencar, Liana (2017)
Introdution: Hansen’s disease is an infecto-contagious, chronic and curable disease, caused by the Mycobacterium Leprae with a preference for the peripheral nervous system. Objectives: To determine the clinical forms and the operational classification of patients suffering from Hansen's disease; to identify the disability grade of patients diagnosed with Hansen’s disease. Methods: Cross-sectional study with a quantitative approach of a descriptive nature performed on 104 patients diagnosed with Hansen’s disease. Most were male, 63 (60.6%), with an average age of 37 years, 49% had pardo complexion and 34.6% had an elementary education level. Data was collected from the: Notifiable Diseases Information System – SINAN in 2014; Simplified Neurologic Assessment Form for assessing the Grade of Disability (Brasil, 2010, p.35), taken from the Guide for Prevention of Disabilities (Brasil, 2008, p. 112-113). Results: The operational classification of patients suffering from Hansen’s disease revealed that 47.1% were paucibacillary while 52.9% were multibacillary and that 31.7% were diagnosed with the Borderline form and 25.9% with the Tuberculoid form. The Physical Disability Grade (PDG) at the time of diagnosis was the following: Grade 0 – 73 (70.20%); Grade 1 - 17 (16.35%); and 9 patients (8.65%) had developed Grade 2 disabilities. The odds ratios significantly indicate that for women with Hansen’s disease the risk of not having physical disabilities at the time of diagnosis is about 4 times higher than it is for men (OR= 3.868; CI 95%=1.316-11.368). Conclusions: The occurrence of disabilities resulting from Hansen’s disease mostly in men is still a public health problem in Brazil. Therefore, active search for cases within the community, examining household contacts, monitoring of patients by the healthcare units, educational campaigns and research with students in schools are examples of policies which should be implemented in order to eradicate this endemic disease and reduce sequelae thereof.